2016
DOI: 10.1080/23311843.2016.1254078
|View full text |Cite
|
Sign up to set email alerts
|

A multi-stakeholder strategy to identify conservation priorities in Peninsular Malaysia

Abstract: Malaysia, with its rapidly growing economy, exemplifies the tensions between conservation and development faced by many tropical nations. Here we present the results of a multi-stakeholder engagement exercise conducted to (1) define conservation priorities in Peninsular Malaysia and (2) explore differences in perceptions among and within stakeholder groups (i.e. government, academia, NGOs and the private sector). Our data collection involved two workshops and two online surveys where participants identified se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Through the problem tree exercise, we acknowledged that in Malaysia, the established mindset of the government and society is to prioritize people's welfare first, and the country's development plans in the past have mostly been human-centric (Nagulendran et al, 2016). After World War II ended in 1945, Malaysia's concern was on alleviating poverty.…”
Section: Discussionmentioning
confidence: 99%
“…Through the problem tree exercise, we acknowledged that in Malaysia, the established mindset of the government and society is to prioritize people's welfare first, and the country's development plans in the past have mostly been human-centric (Nagulendran et al, 2016). After World War II ended in 1945, Malaysia's concern was on alleviating poverty.…”
Section: Discussionmentioning
confidence: 99%
“…This is concerning, as it affects Malaysians perception on how the forestry sector is governed. Nagulendran et al (2016), for instance, engaged with a wide range of stakeholders to identify conservation themes and priorities. They found that members of the government had, on average, more positive opinions on the state of protected areas and wildlife in Malaysia compared to members of NGOs, academia and the private sector.…”
Section: Discussionmentioning
confidence: 99%
“…They found that members of the government had, on average, more positive opinions on the state of protected areas and wildlife in Malaysia compared to members of NGOs, academia and the private sector. However, Nagulendran et al (2016) also found that policy and management of protected areas and wildlife was seen as inadequate by various stakeholders, citing issues such as lack of leadership, ineffective implementation, and conflicting policies. Not only that, in this situation, the people remain powerless to stop any action taken by the state government, as public participation exists only in name and any action cannot be taken without the cooperation and consent of the state government.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations